Bi12Rh3Cu2I5: A 3D Weak Topological Insulator with Monolayer Spacers and Independent Transport Channels - Carrillo-Aravena, Eduardo; Finzel, Kati; Ray, Rajyavardhan; Richter, Manuel; Heider, Tristan; Cojocariu, Iulia; Baranowski, Daniel; Feyer, Vitaliy; Plucinski, Lukasz; Gruschwitz, Markus; Tegenkamp, Christoph; Ruck, Michael (physica status solidi (b), 2022)
Topological insulators (TIs) are semiconductors with protected electronic surface states that allow dissipation-free transport. TIs are envisioned as ideal materials for spintronics and quantum computing. In Bi14Rh3I9, the first weak 3D TI, topology presumably arises from stacking of the intermetallic [(Bi4Rh)3I]2+ layers, which are predicted to be 2D TIs and to possess protected edge-states, separated by topologically trivial [Bi2I8]2− octahedra chains. In the new layered salt Bi12Rh3Cu2I5, the same intermetallic layers are separated by planar, i.e., only one atom thick, [Cu2I4]2− anions. Density functional theory (DFT)-based calculations show that the compound is a weak 3D TI, characterized by (Formula presented.), and that the topological gap is generated by strong spin–orbit coupling (E g,calc. ∼ 10 meV). According to a bonding analysis, the copper cations prevent strong coupling between the TI layers. The calculated surface spectral function for a finite-slab geometry shows distinct characteristics for the two terminations of the main crystal faces ⟨001⟩, viz., [(Bi4Rh)3I]2+ and [Cu2I4]2−. Photoelectron spectroscopy data confirm the calculated band structure. In situ four-point probe measurements indicate a highly anisotropic bulk semiconductor (E g,exp. = 28 meV) with path-independent metallic conductivity restricted to the surface as well as temperature-independent conductivity below 60 K.
CRIS-Team Scopus Importer:2022-04-14